2019
DOI: 10.1016/j.aim.2019.106824
|View full text |Cite
|
Sign up to set email alerts
|

On the level of modular curves that give rise to isolated j-invariants

Abstract: We say a closed point x on a curve C is sporadic if C has only finitely many closed points of degree at most deg (x). Motivated by well-known classification problems concerning rational torsion of elliptic curves, we study sporadic points on the modular curves X 1 (N ). In particular, we show that any non-cuspidal non-CM sporadic point x ∈ X 1 (N ) maps down to a sporadic point on a modular curve X 1 (d), where d is bounded by a constant depending only on j(x). Conditionally, we show that d is bounded by a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The following result is a direct generalization of [9, Lemma 6.2]. Theorem Let H0$H_0$ be a subgroup of GL2(Z/NZ)/{±1}$\operatorname{GL}_2(\mathbb {Z}/N\mathbb {Z})/\lbrace \pm 1\rbrace$.…”
Section: Sporadic CM Points On Modular Curvesmentioning
confidence: 98%
See 1 more Smart Citation
“…The following result is a direct generalization of [9, Lemma 6.2]. Theorem Let H0$H_0$ be a subgroup of GL2(Z/NZ)/{±1}$\operatorname{GL}_2(\mathbb {Z}/N\mathbb {Z})/\lbrace \pm 1\rbrace$.…”
Section: Sporadic CM Points On Modular Curvesmentioning
confidence: 98%
“…By [23, Theorem 3.1] we have J1(N)(Q)$J_1(N)(\mathbb {Q})$ is finite. From this it follows — see, for example, [9, Theorem 4.2] — that δ(X1false(Nfalse))=γQ(X1false(Nfalse))$\delta (X_1(N)) = \gamma _{\mathbb {Q}}(X_1(N))$. Comparing the work of [24] to our own calculations, we find that dCM(X1false(Nfalse))<γQ(X1false(Nfalse))$d_{\operatorname{CM}}(X_1(N)) &lt; \gamma _{\mathbb {Q}}(X_1(N))$.$\Box$…”
Section: Computationsmentioning
confidence: 99%
“…To emphasize that a resolution of Fermat equation with prime exponent over the fields K considered above is a task worth pursuing, we will show that such a resolution is possible if we assume a folklore conjecture (see [2]) motivated by a question of Serre.…”
Section: Serre's Uniformity Conjecture and Asymptotic Fermatmentioning
confidence: 99%
“…Let K = Q( √ −d), where d ∈ {1, 2, 7}. Assume Conjecture 2.2 holds for K. If p ≥ 5 is a rational prime number, then the equation (2) a p + b p + c p = 0 has no solutions a, b, c ∈ K \ {0}.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to answer Question 1.1 more generally, it seems likely we will need to have a better understanding of sporadic points on modular curves. To this end, Bourdon, Ejder, Liu, Odumodu, and Viray [2] have recently shown that, assuming Serre's uniformity conjecture, the number of sporadic j-invariants (j-invariants corresponding to sporadic points on some modular curve X 1 (N )) in a given number field is finite. Regarding Question 1.2, Merel [31] answered it in the affirmative.…”
Section: Previous Work and Motivationmentioning
confidence: 99%